Claiming the City: How India’s Urban Spaces Exclude Women and How to Fix Them, A Case Study of New Delhi - Anusha Muralidhar (International Journal of Urban Design and Development, 2026)
This paper analyses the layered risks, vulnerabilities, and everyday negotiations faced by women in open public spaces in diverse sites across India, with New Delhi as a representative and highly stratified urban case. It examines how specific Urban design competences, planning attitudes, and governance mechanisms have in the past resulted in exclusionary and not safe environments for women. Based on crime reports, government statistics, academic literature, and field-based observations, the article shows that despite progressive legislation and numerous policy initiatives, women’s mobility, autonomy, and spatial citizenship continue to remain constricted due to a lack of infrastructure for them, coupled with patriarchal planning paradigms as well as weak implementation of safety-oriented measures. Using an intersectional analytical perspective, this paper provides evidence on how caste, class, religion, and other social identities such as disability and LGBTQ identity intersect to magnify women’s vulnerability to urban risks and perpetuate structural forms of disadvantage. Positioning these layered inequalities in relation to spatial and design failure, the paper contends that the exclusion of women from public space is both socially entrenched and institutionally perpetuated by planning and regulatory regimes. Cross-national lessons learned from feminist urban interventions and gender-responsive policies in Latin America, Sub-Saharan Africa, and East Asia show the potential for participatory design, community- based audits, and comprehensive approaches to safety to change the perception of place. Serving as a bridge between theory and practice, the paper develops an approach towards feminist and gender-sensitive urbanism that prioritizes lived experiences, accessibility, care, and collective safety as key planning principles. It demands institutional transformation as well as multi-sectoral coordination through mechanisms of strong accountability, which is not beholden to protectionist logics but rather enables women to exercise visibility, agency, and substantive rights in the shaping of just and sustainable urban futures.
Keywords: Economic engagement; Urban spaces; Women Safety; landscape; urban planning